Daily Life, Transformations and Emotions during the Pandemic: Stories from Home Referrals - García Bastán, Guido (2025)
In this paper, we present part of the results of a project aimed at analyzing inequalities and access to rights during the COVID-19 pandemic in households in the city of Córdoba, Argentina. Following the guidelines of Grounded Theory, from a qualitative strategy based on interviews with 40 household referents, we analyze the transformations in daily life, the differential experiences in relation to specific social markers and the role of emotions in the configuration of these experiences. Our findings indicate that, for all socioeconomic levels, confinement was an intensive experience in terms of the reorganization of household units. The analysis of markers of generation, gender and socioeconomic level reveals unequal ways of experiencing the most critical moments of the pandemic and confinement. Likewise, the exploration of the emotional dimension in the testimonies made it possible to reconstruct the evaluations that different sectors made of the role played by the State during the pandemic, a central aspect to advance in the evaluation of public policies oriented to the care of the population.